US High Tariff on India - Role of Indigenous Industries as a Mitigator and Revenue Generator for India - Rais, Shirin; Asif, Mohammad (Theoretical and Practical Research in Economic Fields; Vol 16 No 4 (2025): TPREF Special Issue, Volume XVI, Issue 4(36), Winter 2025, 2025)
The current high tariff regime of the United States (US) marks the return of the restated version of the mercantilist era aimed at making US richer by draining wealth from other countries through tariff hikes because of which the world may move towards deglobalization, disrupting the global value chains, and may force other countries also to turn protectionist by making international trade expensive. The paper suggests that the growth of Indian indigenous industries will mitigate the impact of US high tariffs on Indian economy. Also, due to the prospects of deglobalization, foreign trade as a source of revenue for India seems bleak, therefore, participation of indigenous industries in economic activities should be further promoted by increasing their domestic market share and substituting these indigenous products for foreign products. This will raise revenue, provide employment opportunities to the population mainly residing in rural India and will help in attaining the goal of inclusive growth because India is the only country in the world where varieties of mostly environmentally friendly internationally acclaimed indigenous products, like Khadi, other handlooms, handicrafts, spices, teas, carpets, metalcrafts, tribal art and crafts, AYUSH, agricultural products, etc are produced in different corners of the country. The paper asserts that the ‘Make in India’ campaign will be more successful in achieving ‘Self-Reliance’ than ‘Make in US’ campaign, which is dramatically failing, as the major burden of this higher tariff is falling on the US citizens, due to the failure of the working of ‘Make in US’ campaign in transforming US into a manufacturing hub.